20 years of crystal hits: progress and promise in ultrahigh‐throughput crystallization screening. Issue 3 (27th February 2023) - Lynch, Miranda L.; Snell, M. Elizabeth; Potter, Stephen A.; Snell, Edward H.; Bowman, Sarah E. J.
Abstract : The crystallization facility at Hauptman–Woodward Medical Research Institute, now the National High‐Throughput Crystallization Center, has served the structural biology community for over two decades. The lessons learned from our high‐throughput crystallization services, current operations and capabilities are described, together with a vision for the future of crystallization. Abstract : Diffraction‐based structural methods contribute a large fraction of the biomolecular structural models available, providing a critical understanding of macromolecular architecture. These methods require crystallization of the target molecule, which remains a primary bottleneck in crystal‐based structure determination. The National High‐Throughput Crystallization Center at Hauptman–Woodward Medical Research Institute has focused on overcoming obstacles to crystallization through a combination of robotics‐enabled high‐throughput screening and advanced imaging to increase the success of finding crystallization conditions. This paper will describe the lessons learned from over 20 years of operation of our high‐throughput crystallization services. The current experimental pipelines, instrumentation, imaging capabilities and software for image viewing and crystal scoring are detailed. New developments in the field and opportunities for further improvements in biomolecular crystallization are reflected on.